Colour appearance in led lighting - Ixtaina, Pablo Ruben (2010)
The paper shows a comparative study of colour comparison between white LED lamps and conventional ones (incandescent and compact fluorescent). The LED lamps used were a model designed by the direct replaces of halogen incandescent lamps. The technology used for white light generation was based on short waves emitter chips and secondary emission. As result of the experience, significant object colour coordinates displacements in LEDs lighting were observed. As it was predictable from LEDs spectral distribution, orange – red colours were poorly reproduced. However, the subjective experience did not show a remarkable preference to the conventional light sources. Furthermore, several observers qualified the objects under LEDs light as “more naturals”.